2015
DOI: 10.1016/j.atherosclerosis.2015.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Increased aldehyde-modification of collagen type IV in symptomatic plaques – A possible cause of endothelial dysfunction

Abstract: Increased aldehyde-modification of collagen type IV in symptomatic plaques -A possible cause of endothelial dysfunction.Dunér, Pontus; Goncalves, Isabel; Grufman, Helena; Edsfeldt, Andreas; To, Fong; Nitulescu, Mihaela; Nilsson, Jan; Bengtsson, Eva Link to publication Citation for published version (APA): Dunér, P., Goncalves, I., Grufman, H., Edsfeldt, A., To, F., Nitulescu, M., ... Bengtsson, E. (2015). Increased aldehyde-modification of collagen type IV in symptomatic plaques -A possible cause of endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…We have recently shown that MDA-modified collagen (MDA-collagen) type IV is present in lipid-rich regions of human plaques, supporting the notion that LDL oxidation induces MDA modification of ECM proteins [32]. Of interest, the level of autoantibodies against MDA-collagen type IV in plasma correlated with the amount of MDA-collagen type IV in the lesions [32]. Of interest, the level of autoantibodies against MDA-collagen type IV in plasma correlated with the amount of MDA-collagen type IV in the lesions [32].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…We have recently shown that MDA-modified collagen (MDA-collagen) type IV is present in lipid-rich regions of human plaques, supporting the notion that LDL oxidation induces MDA modification of ECM proteins [32]. Of interest, the level of autoantibodies against MDA-collagen type IV in plasma correlated with the amount of MDA-collagen type IV in the lesions [32]. Of interest, the level of autoantibodies against MDA-collagen type IV in plasma correlated with the amount of MDA-collagen type IV in the lesions [32].…”
Section: Introductionsupporting
confidence: 54%
“…In individuals with diabetes, glycosylation of collagen type IV interferes with the disposition and integrity of the protein which could affect the normal function of basement membranes [33]. We have recently shown that MDA-modified collagen (MDA-collagen) type IV is present in lipid-rich regions of human plaques, supporting the notion that LDL oxidation induces MDA modification of ECM proteins [32]. Furthermore, MDA-collagen type IV was increased in carotid plaques from symptomatic patients compared to plaques from asymptomatic patients.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…They may also include altered covalent cross linking of collagens by lysyl oxidases (LOX) and/or oxidative modification e.g. by reactive aldehydes originating from oxidized low-density-lipoprotein [41] within the ECM. Collagens influence the function and activity of cells in the arterial wall, i.e.…”
Section: Discussionmentioning
confidence: 99%